2022
DOI: 10.3389/fphar.2022.831311
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Ca2+-Activated Cl− Channel TMEM16A Mediated by Angiotensin II in Cirrhotic Portal Hypertensive Mice

Abstract: Portal hypertension is defined as an increased pressure in the portal venous system and occurs as a major complication in chronic liver diseases. The pathological mechanism underlying the pathogenesis and development of portal hypertension has been extensively investigated. Vascular tone of portal vein smooth muscles (PVSMs) is regulated by the activities of several ion channels, including Ca2+-activated Cl− (ClCa) channels. TMEM16A is mainly responsible for ClCa channel conductance in vascular smooth muscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…We previously reported that spontaneous contractions were reduced by 30 µM T16A inh -A01 (a specific TMEM16A Cl Ca channel blocker). 13) In Cav1-KO PVSMs, their amplitude was increased (0.345 ± 0.071 mN, n = 4, p = 0.038; Figs. 1A, B), whereas their frequency was not altered (25.9 ± 3.1 min −1 , n = 4, p = 0.357; Figs.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…We previously reported that spontaneous contractions were reduced by 30 µM T16A inh -A01 (a specific TMEM16A Cl Ca channel blocker). 13) In Cav1-KO PVSMs, their amplitude was increased (0.345 ± 0.071 mN, n = 4, p = 0.038; Figs. 1A, B), whereas their frequency was not altered (25.9 ± 3.1 min −1 , n = 4, p = 0.357; Figs.…”
Section: Resultsmentioning
confidence: 88%
“…Enhanced Spontaneous PVSM Contractions in Cav1-KO Mice PVSMs exhibit spontaneous and periodic contractions without any stimulations and spontaneous contractions are sensitive to Cl Ca blockers. 13) To demonstrate the direct involvement of Cav1 in spontaneous PVSM contractions, contractile responses were recorded in the PVSMs of WT and Cav1-KO mice. In WT PVSMs, the mean amplitude of spontaneous contractions was 0.163 ± 0.030 mN (n = 5; Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations